Phylogeographic Analyses of the Shortfin Mako, Isurus oxyrinchus Rafinesque, 1810 (Chondrichthyes: Lamniformes) from the Central Mediterranean Sea, a Critically Endangered Species in the Region - Noel Vella; Adriana Vella (Fishes, 2023)
The Shortfin mako shark, Isurus oxyrinchus Rafinesque, 1810, is a globally distributed highly migratory pelagic shark species, occurring mostly in temperate and tropical regions, including the Mediterranean Sea where it is by-caught during fishing activities targeting other economically important fish species. The aim of this study is to investigate the genetic connectivity of the Shortfin mako from the central Mediterranean Sea to previously studied populations. The mtDNA control region (CR), 977 bp, of 37 I. oxyrinchus specimens collected between 2004 and 2012 from landings in Malta were analysed, and we identified nine haplotypes, including three newly discovered haplotypes that may be unique to the Mediterranean Sea and which represent 16.7% of the studied individuals. These haplotypes, together with variations in haplotype frequencies, led to significant FST and ϕST values between the Mediterranean population and other global populations, with the exception of that from the north Atlantic Ocean. This study provides the first insight of the mtDNA CR diversity of this critically endangered species in the Mediterranean Sea and highlights the importance of conserving this species in the region.